Implementasi Model Cooperative Integrated Reading and Composition (CIRC) untuk Meningkatkan Keterampilan Membaca Pemahaman dan Bernalar Kritissiswa Sekolah Dasar pada Pembelajaran Agama Islam di Kecamatan Leuwiliang Kabupaten Bogor - Imas Komalasari; Chaira Saidah Yusrie; Yusi Srihartini (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The problem addressed in this study is the low level of reading comprehension and critical thinking skills among elementary school students, particularly in the subject of Islamic Education (PAI). Many students can only string words together without understanding their meanings, which adversely affects their learning outcomes. This issue is exacerbated by the conventional teaching methods currently in use, making the learning experience less engaging and even boring for students. Therefore, there is a need for a learning approach that can enhance students' reading comprehension and critical thinking skills, one of which is the implementation of the Cooperative Integrated Reading and Composition (CIRC) model. This research aims to answer several questions: (1) How is the implementation of the Cooperative Integrated Reading and Composition model in improving students' reading comprehension skills? (2) How does the implementation of Cooperative Integrated Reading and Composition (CIRC) enhance students' critical thinking skills? (3) What challenges do teachers face in applying the Cooperative Integrated Reading and Composition (CIRC) model? The research method employed is qualitative with a descriptive approach. Data collection was carried out through observations, interviews, and documentation. The subjects of the study are Islamic Education teachers in the Leuwiliang district of Bogor Regency. The findings indicate that the application of the CIRC model effectively enhances students' reading comprehension and critical thinking skills. Students become more active in learning, capable of collaborating in groups, and show improved understanding of the material. However, some challenges, such as limited teaching media and the readiness of teachers to implement this model, present specific obstacles during its application.